Meningkatkan Kemampuan Siswa Menulis Wacana Berbentuk Descriptive Melalui Model Pembelajaran Describe Pictures di Kelas VII 6 SMPN 3 Tangerang Selatan - Nenden Hezrianthi (LAP4B, 2024)
The goal to be achieved in this study is to improve students' ability to compile descriptive texts by developing learning strategies and learning models that are effective, efficient and fun and involve students actively in communication activities by expressing their ideas, opinions and feelings simply in writing. This research is a Classroom Action Research which is carried out by following the procedures of planning, action, observation, reflection or evaluation which is carried out repeatedly in the form of cycles. The results showed that through the describe pictures learning model, there was an increase in the percentage of student activeness in learning from 43.47% in cycle 1 to 71.73% in cycle 2. Student test results, the percentage of student scores below KKM from 89.14% in cycle 1 to 41.31% in cycle 2, this also means the percentage of students who have scores equal to or above KKM from 10.87% in cycle 1 to 58.67% in cycle 2. While the average result of the test writing score from 62.72 in cycle 1 to 70.12 in cycle 2. This means that the use of the Describe Pictures Learning Model can improve the ability of grade VII.6 students of SMPN 3 Tangsel in semester 2 of the 2021-2022 academic year.